Arabisasi Sebagai Strategi Komunikasi: Analisis Relevansi dalam Pidato Abu Ubaidah - Prakoso, Ahmad Bagas (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2025)
This study aims to analyze the use of arabization  as a communication strategy in the speeches of Abu Ubaidah, the spokesman of the Al-Qassam Brigades, by highlighting the relevance of arabized terms in reinforcing political messages to the Palestinian audience. Using a descriptive qualitative method, the research applies Dan Sperber and Deirdre Wilson’s Relevance Theory along with lexicological and phonological approaches. The primary data were obtained from transcripts of Abu Ubaidah’s speeches sourced from the YouTube channels of AlJazeera Arabic and Al Arabiya, which were analyzed to identify arabized terms and their lexical and phonological adaptation processes. The findings reveal that terms such as “التكتيك” (tactic), “الإستراتيجية” (strategy), and “السيناريو” (scenario) were strategically chosen to enhance the relevance of the message, strengthen emotional and political resonance with the audience, and convey modern and professional connotations compared to classical arabic equivalents. Phonological adaptations further ensure that these terms are linguistically and culturally accepted. Overall, the study confirms that arabization not only strengthens political messaging but also creates strong contextual effects aligned with communicative goals, contributing significantly to the study of pragmatics, lexicology, phonology, and political communication strategies.